Alternative Dispute Resolution vs. Judicial Conciliation in the Civil Process of Transit States: A Comparative Study - Tykhanskyi, Oleksandr B.; Khotynska-Nor, Oksana Z.; Vasylyna, Nataliia V.; Bondarieva, Maria V. (International Journal of Criminology and Sociology, 2021)
The study investigates the current problems of judicial and extra-judicial conciliation procedures (alternative ways of resolving civil disputes) in states that have just started implementing such a procedural tool. Despite the fact that the term "conciliation procedures” is actively used in the science of civil procedure, this category is rather vague in countries that are just beginning to apply judicial conciliation in parallel with other conciliation procedures. Priority attention is focused on practical, legislative, and scientific problems of applying this procedural tool for rapid resolution of legal conflicts in Ukraine, as a state that only in 2017 (and in fact since the beginning of 2018) introduced this legal innovation. The purpose of the study is to elaborate on the legal nature and correlation between judicial conciliation (settlement of civil disputes with the participation of a judge under Ukrainian legislation) and alternative ways of resolving civil disputes. The study is based on several scientific methods that have identified the logic and general direction of knowledge of the problem of judicial conciliation. In particular, to determine the legal nature, essence, criteria of correlation, and delimitation of alternative dispute resolution and judicial conciliation, the study used the dialectical scientific cognition method. The study engages in a comparative study of the statutory regulation of similar procedures in the Russian Federation and Belarus legislation. It is concluded that alternative dispute resolution and judicial conciliation are closely interrelated and, depending on their types, can sometimes manifest themselves as synonymous categories or institutions of law.